Encountering grief and loss [ - VEA Australia (Australia : VEA Australia / New Zealand Pty Ltd, 2010)
As health professionals we must support patients and their families, careers and friends as they grapple with their own personal experiences of loss and grief. In this insightful program we take a holistic approach to understanding and responding to loss and grief. We speak frankly with Christine McMahon, who lost her only son in Victoria's Black Saturday bushfire in 2009, about her personal experience of extreme loss and grief. Experts in counselling and palliative care help us to recognise loss and grief and employ practical strategies to support a person who is battling through one the most difficult times in their life.
Program support notes available on www.VEA.com.au/HealthCare
Keywords: Bereavement; Counseling; Grief